2010
DOI: 10.1111/j.1365-2885.2010.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen in piglets: enantioselective pharmacokinetics, pharmacodynamics and PK/PD modelling

Abstract: The chiral pharmacokinetics and pharmacodynamics of ketoprofen were investigated in a placebo-controlled study in piglets after intramuscular administration of 6 mg/kg racemic ketoprofen. The absorption half-lives of both enantiomers were short, and S-ketoprofen predominated over R-ketoprofen in plasma. A kaolin-induced inflammation model was used to evaluate the anti-inflammatory, antipyretic and analgesic effects of ketoprofen. Skin temperatures increased after the kaolin injection, but the effect of ketopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 49 publications
6
52
0
Order By: Relevance
“…The pharmacokinetic parameters of both enantiomers after IM administration were similar to those reported by Fosse [31] in piglets, despite the pigs in our study being older than those used in their study. T max and AUC S /AUC R ratio after oral administration were higher in our study than in the study reported by Neirinckx [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The pharmacokinetic parameters of both enantiomers after IM administration were similar to those reported by Fosse [31] in piglets, despite the pigs in our study being older than those used in their study. T max and AUC S /AUC R ratio after oral administration were higher in our study than in the study reported by Neirinckx [14].…”
Section: Discussionsupporting
confidence: 89%
“…The absolute bioavailability of both ketoprofen enantiomers after IM administration is suggested to be almost complete [13,31]. After PO administration the bioavailability is reported to be approximately 85 % for both enantiomers [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic levels have been reported for ketoprofen enantiomers in pigs, with concentrations of 26.7 μg/mL for S-ketoprofen and 1.6 μg/mL for R-ketoprofen. 31 Maximum concentrations were 7.42 mg/L for S-ketoprofen and 2.55 mg/L for R-ketoprofen when administered orally in pigs. 32 The concentration of ketoprofen in plasma was 4.5-8.4 μg/mL in our sheep at 2 h after administration and R-ketoprofen has been recorded as the most prominent enantiomer found in sheep.…”
Section: Discussionmentioning
confidence: 98%
“…To determine the analgesic efficacy of ketoprofen in piglets, a handheld algometer was used to quantify mechanical thresholds pre- and posttreatment. The higher thresholds recorded in the ketoprofen-treated group compared to the placebo group suggested an anti-nociceptive effect between 12 and 24 h after drug administration, through the reduction of sensitivity of the peripheral nerve receptors (136). …”
Section: Pain Assessment In Pigsmentioning
confidence: 99%